Grain Legume Yield Responses to Rhizobia Inoculants and Phosphorus Supplementation Under Ghana Soils: A Meta-Synthesis - Buernor, Alfred Balenor; Kabiru, Muhammad Rabiu; Bechtaoui, Noura; Jibrin, Jibrin Mohammed; Asante, Michael; Bouraqqadi, Anis; Dahhani, Sara; Ouhdouch, Yedir; Hafidi, Mohamed; Jemo, Martin (Frontiers in Plant Science, 2022)
A separate number of studies have been conducted on the effects of rhizobia (Rhz) inoculants, phosphorus (P) management, and combined application of Rhz and P fertilizer on grain legumes yield enhancement across soils of Ghana and elsewhere. However, the extent to which the various inoculated Rhz strains, P application, the combined application of Rhz x P contribute to improving yield performed on a comprehensive analysis approach and profit farmers are yet to be understood. This study reviewed different experimental studies conducted in soybean (Glycine max (L.) Merr.), cowpea (Vigna unguiculata [L.] Walp), and groundnut (Arachis hypogaea [L.]) to which Rhz inoculants, P supplements, or Rhz x P combination were applied to improve yield. Multiple-step search combinations of published articles and multivariate analysis computing approaches were used to assess the effects from Rhz inoculation, P application, or both application of Rhz and P on yield variation. The random forest (RF) regression model was further employed to quantify the relative importance of various predictor variables on yield. The meta-analysis analysis results showed that cowpea exhibited the highest (61.7%) and groundnut (19.8%) the lowest average yield change. The RF regression model revealed that combined application with Rhz and P combination (10.5%) and Rhz inoculation (7.8%) as explanatory variables predicted the soybean yield variation. The Rhz × P combination, Rhz inoculation, genotype wang-Kae explained respectively 11.6% followed by10.02%, and 8.04%, respectively yield variability in cowpea. Yield inoculation responses by BR 3299, KNUST 1002, and KNUST 1006 strains increased by 1.48-, 1.26- and 1.16-fold over the non-inoculated cowpea plants, respectively. KNUST 1006 strain exhibited the highest yield increase ratio (1.3-fold) in groundnut plants. A superior effect of combined application with Rhz inoculants and P-fertilizers was observed over Rhz inoculant and P supplementations alone in soybean and cowpea plants. The liquid inoculation method resulted in a higher yield change over the peat under cowpea plants. The meta-synthesis result provides vivid evidence of a positive effect of Rhz inoculation and P management at scale to support decision-makers in creating sustainable outcomes grain legume intervention to profit smallholders of Ghana.